2014
DOI: 10.1007/s40097-014-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of chlorophenols from aqueous solution over amino-modified ordered nanoporous silica materials

Abstract: The capability of the adsorption of 2-chlorophenol (2-CPh) and 2,4-dichlorophenol (2,4-DCPh) from aqueous solutions with mesoporous silica material MCM-48 after functionalizing with amine groups, such as 3-(trimethoxysilyl)propyl amine and tetraethylenepentamine, was investigated in this study. It was found that amino-modified ordered mesoporous silica materials show significant adsorption for 2-CPh and 2,4-DCPh. This is possible due to the alkaline and acid interactions among the amine functional groups and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…It is known that amine groups are effective for the adsorption of organic molecules because of their possible charge association and great adsorption energy. Some examples relate to the adsorption of chlorophenols like 2-chlorophenol (2CPh) and 2,4-dichlorophenol (2,4-DCPh) on a mesoporous silica functionalized by 3-(trimethoxysilyl)propylamine and tetraethylenepentamine (Ghaffari et al 2014). Amino modiefied SBA-15 material was used also as an effective nanosorbent for the removal of halophenols from wastewater (Anbia and Amirmahmoodi 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that amine groups are effective for the adsorption of organic molecules because of their possible charge association and great adsorption energy. Some examples relate to the adsorption of chlorophenols like 2-chlorophenol (2CPh) and 2,4-dichlorophenol (2,4-DCPh) on a mesoporous silica functionalized by 3-(trimethoxysilyl)propylamine and tetraethylenepentamine (Ghaffari et al 2014). Amino modiefied SBA-15 material was used also as an effective nanosorbent for the removal of halophenols from wastewater (Anbia and Amirmahmoodi 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[38] However, the adsorption of organic substances on these adsorbents tends to be low (in terms of Q8) mainly because of the non-specific nature of the binding interactions between the adsorbent and adsorbate. [55] A notable result in this field was reported by Qin et al, [56] who showed that the adsorption of CP on mesoporous SBA-15 (Santa Barbara Amorphous) is increased as the number of chlorine substitutes on the phenol ring is increased. [55] A notable result in this field was reported by Qin et al, [56] who showed that the adsorption of CP on mesoporous SBA-15 (Santa Barbara Amorphous) is increased as the number of chlorine substitutes on the phenol ring is increased.…”
Section: Teos-zn Versus Mesoporous Hybrid Xerogels and Other Adsorbentsmentioning
confidence: 96%
“…Various physical and chemical treatment techniques such as catalytic oxidation, photocatalytic, membrane separation, biodegradation, solvent extraction and adsorption have been used for the reduce of organic pollutants from water [3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of activated carbons is restricted due to their micropore size, weak adsorption selectivity, poor mechanical strength, and inefficient regeneration [9,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation